Willow - Hoban, Julia (New York : Dial Books, 2009)
Sixteen-year-old Willow, who was driving the car that killed both of her parents, copes with the pain and guilt by cutting herself, until she meets a smart and sensitive boy who is determined to help her stop.
Keywords: Cutting (Self-mutilation) -- Juvenile fiction; Self-mutilation -- Juvenile fiction; Guilt -- Juvenile fiction; Grief -- Juvenile fiction; Orphans -- Juvenile fiction